Breast Cancer Phenotype Associated With Li-Fraumeni Syndrome: A Brazilian Cohort Enriched by TP53 p.R337H Carriers - Sandoval, Renata Lazari; Polidorio, Natalia; Leite, Ana Carolina Rathsam; Cartaxo, Mariana; Pisani, Janina Pontes; Quirino, Carla Vanessa; Cezana, Loureno; Pereira, Natálya Gonçalves; Pereira, Allan Andresson Lima; Rossi, Benedito Mauro; Achatz, Maria Isabel (Frontiers in Oncology, 2022)
Breast cancer (BC) is the most prevalent malignancy in women with Li-Fraumeni syndrome (LFS). The literature on BC in LFS is limited due to its rarity worldwide. A TP53 founder pathogenic variant (c.1010G>A; p.R337H) is responsible for the higher prevalence of this syndrome among women of Brazilian ancestry. Purpose The aim of the study was to describe the BC phenotype expressed by Brazilian female LFS carriers and compare the data between p.R337H and other TP53 germline pathogenic/likely pathogenic variants (non-p.R337H carriers). Methods We searched for cases of TP53 germline pathogenic/likely pathogenic variant carriers affected by BC included between 2015 and 2020 in the BLiSS (Brazilian Li-Fraumeni Study) registry at the Sírio-Libanês Hospital. Results Among 163 adult female carriers from the registry, 91 (56%) had received a BC diagnosis, including 72 p.R337H carriers. BC was the first cancer diagnosed in 90% of cases. Early onset BC (age ≤45 years) was diagnosed in 78.2% of cases (11.5% <31 years; 66.7% 31–45 years; 21.8% >45 years). The median age of BC diagnosis for p.R337H carriers was 39.5 years (range 20–69 years) compared to 34 years (range 21–63 years) for non-p.R337H carriers (p = 0.009). In total, 104 breast tumors were observed in 87 women. Bilateral BC was observed in 29.3% of cases. Histology was available for 96 tumors, comprising 69 invasive breast carcinomas, which were mostly invasive ductal carcinomas (95.6%), 25 ductal in situ carcinomas and 2 soft-tissue sarcomas. Overall, 90.5% of invasive breast carcinomas were hormone receptor (HR)-positive, 39.5% were human epidermal growth factor receptor 2 (HER2)-positive, and 32.8% showed HR and HER2 co-expression. In addition, 55.4% of patients opted for contralateral prophylactic mastectomy after a first BC diagnosis. There were no significant differences in the risk of developing contralateral BC or in the immunohistochemical profile between p.R337H and non-p.R337H groups. Conclusions The expressed phenotype of p.R337H is similar to that of other TP53 pathogenic/likely pathogenic variants, except for an average older age at the onset of disease; however, this is still younger than the general population.